Determination of bacteriocin-encoding genes of lactic acid bacteria isolated from traditional dairy products of Luxor province, Egypt - Rasha Mohamed Refay; Hala Mohamed Abushady; Sara Adel Amer; Mahmoud Ahmed Mailam (SpringerOpen, 2020)
Abstract Background Researchers have focused on isolating and identifying the bacteriocin producing lactic acid bacteria from various food systems especially dairy products. Molecular techniques have been recently used for rabid identification of bacteriocins rather than time-consuming biochemical characters. Global climate disturbances can affect the diversity of beneficial microorganisms in dairy and their products, especially lactic acid bacteria, so it is worth to evaluate their bacteriocinogenicity in different climates. Thus, the aim of this study was to screen for predominant bacteriocin producing lactic acid bacteria (LAB) in traditional dairy products of Luxor governorate at Upper Egypt and determine their bacteriocin-encoding genes. Results Eighty-six strains of the LAB were isolated from raw milk and traditional dairy product of Luxor province, Egypt, in which 76.1% and 23.9% were identified as lactic acid bacilli and cocci, respectively. On the basis of their antibacterial potentials, 30 out of 68 LAB isolates were found to be antimicrobial producers. These isolates exhibited a potential antibacterial activity against Salmonella paratyphi B, Escherichia coli, Staphylococcus aureus, and Proteus mirabilis, except for Listeria monocytogenes. LAB isolates were analyzed using species-specific PCR; results emphasized that 22 of isolates were identified as Lactobacillus plantarum, while 8 were Leuconostoc mesenteroides. According to the sequencing of isolates, two strains named Lactobacillus plantarum Egypt 2018 (accession no. MH817034) and Leuconostoc mesenteroides Egypt 2018 (accession no. MH817035) were identified. Detection of bacteriocin-encoding genes was performed by polymerase chain reaction (PCR). The results emphasized that almost all tested Lb. plantarum strains (n = 10) possess both plnA and plnEF genes, whereas the gene encoding mesentericin Y105 was detected in one Lc. mesenteroides of the examined isolates. Conclusions This study was effective for the rapid detection of bacteriocin producing strains within dairy products. Extracted bacteriocin could be a valuable source of natural food biopreservative.